FERTILITY RESPONSE IN POSTPARTUM SUBESTRUS SURTI BUFFALO SUBJECTED TO HEATSYNCH ± PRID FIXED-TIME AI PROTOCOL - SAXENA, S; KHASATIYA, C T; SAVANI, H R; PATEL, M D; KHARADI, V B (The Indian Journal of Animal Reproduction, 2022)
Eighteen postpartum subestrus (>45 d postpartum) Surti buffalo were equally divided into three groups to evaluate the efficacy of fixed time AI (FTAI) protocols viz. Heatsynch and Heatsynch + PRID (Progesterone Release Intra-vaginal Device), and the third group was not subjected to any treatment protocol (control). In both FTAI groups, the buffalo were administered (i.m.) GnRH analogue (0.01 mg, Inj. Busereline acetate) on day 0, PGF2α analogue (500 μg, Inj. Cloprostenol sodium) on day 7 and estradiol benzoate (0.5 mg) on day 8. In addition, in Heatsynch + PRID group, intra-vaginal PRID implant (0.96 g, progesterone) was inserted for 7 days. In both FTAI groups, inseminations were carried out twice on day 10. In the control group, inseminations were done at spontaneous estrus. In all the groups, the buffalo failing to conceive were re-inseminated at subsequent spontaneous estrus. The overall percentage of buffalo getting conceived in Heatsynch, Heatsynch + PRID and control group was 100, 83.3 and 66.7%, respectively. In brief, Heatsynch protocol, being cost effective, can be recommended to improve fertility status of postpartum subestrus Surti buffalo.